Pengembangan Model Transportasi Kota dalam Menghadapi Tantangan Aglomerasi Kota - Teguh Budi Prasetya; Winarna Winarna (Jurnal Maksipreneur, 2014)
Agglomeration cities not only cause physical problems and instrumental, but also cause problems in the implementation of urban transport. Existing institutional reality no longer able to provide transport services across the city, whose scope is in the surrounding area. This paper sourced on the results of the first study of two years of research, Based on the results of previous studies, coupled with best transportation practices of Singapore and Bogotta, then drafted Urban Transport Model. A model that can address the challenges of the city agglomeration. Four cities sampled (Jakarta, Yogyakarta, Semarang, and Cilacap) seen that every city has its own challenges. Institutional existing transportation is basically in the form of the city's response to answer the challenge. Commitment of all stakeholders will largely determine the success of institutional development.